2007
DOI: 10.1653/0015-4040(2007)90[171:eoatoc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acclimation to Outdoor Conditions on the Sexual Performance of Mass-Produced Medflies (Diptera: Tephritidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Cages are kept in rooms at 24 °C and 60% RH. The temperature is adjusted to 20 °C during the winter season for better acclimation to outdoor conditions [ 22 ]. Adults develop under these conditions until they are released in the field, 48 h after achieving 50% of emerged pupae.…”
Section: Development Of Pupae and Emergence Of Sterile Adultsmentioning
confidence: 99%
“…Cages are kept in rooms at 24 °C and 60% RH. The temperature is adjusted to 20 °C during the winter season for better acclimation to outdoor conditions [ 22 ]. Adults develop under these conditions until they are released in the field, 48 h after achieving 50% of emerged pupae.…”
Section: Development Of Pupae and Emergence Of Sterile Adultsmentioning
confidence: 99%
“…In the former, most matings occurred during the early part of the night (18:00 h) while in the latter, peak mating was attained only 2 h later (20:00 h), and there were significantly fewer matings. Mating behavior characteristics of massreared and sterile insects in a natural environment may be influenced by acclimatization to outdoor conditions (Pereira et al 2007). For example, Judd & Gardiner (2006) state that temperature and light transitions are common in the field as the night progresses and hence may be responsible for differences in response of mass-reared and sterile strains to these changes when released into the field.…”
Section: Effect Of Radiation Treatment On Mating Competitive-nessmentioning
confidence: 99%
“…They further state that mass-rearing could possibly affect temperature thresholds for general activity or dispersal from release locations. Pereira et al (2007) reported that intense selection pressures imposed by rearing conditions lead to shift the sequence and timing of mating away from that which is normally exhibited in the wild. The significantly early mating and large number of matings for both non-irradiated laboratory and irradiated laboratory adults in the laboratory compared with the field are indicative of adaptation to laboratory conditions, where emphasis is on high reproduction rate, earlier and shorter mating (Iwahashi 1996;Matos et al 2000).…”
Section: Effect Of Radiation Treatment On Mating Competitive-nessmentioning
confidence: 99%
“…Estos resultados son similares a los obtenidos en C. capitata, donde machos de cría mantenidos por 0, 1 y 3 días que no mostraron un incremento en su desempeño sexual (Pereira et al 2007). Sin embargo, en esta investigación se menciono la necesidad de estudiar periodos de tiempo más largos como los evaluados en este estudio.…”
Section: Discussionunclassified
“…En algunas especies, para un mejor desempeño sexual, los insectos de cría son previamente aclimatados a campo. Si bien para A. ludens (Meza y Díaz 2006) y A. obliqua (Meza et al 2002) se reporta una aclimatación de dos días antes de la prueba, existe escasa información sobre el efecto de esta medida, mientras que para Ceratitis capitata (Wiedemann) pruebas preliminares reportan que la aclimatación de machos a 0, 1 y 3 días no confiere ventaja en su comportamiento sexual (Pereira et al 2007). En esta investigación evaluamos el desempeño sexual de machos de cría estériles de A. obliqua mantenidos bajo condiciones de campo durante varios periodos de tiempo.…”
Section: Introductionunclassified